Successful pancreas preservation by a perfluorocarbon-based one-layer method for subsequent pig islet isolation. - Brandhorst, D; Iken, M; Brendel, MD; Bretzel, R; Brandhorst, H (2005)
BACKGROUND: The oxygenation of human pancreas by the two-layer method (TLM) during cold storage was recently established for clinical islet transplantation. Simplification of TLM would facilitate the application of perfluorocarbon (PFC) as a regularly used preservation solution for subsequent islet transplantation. The present study examined whether PFC can be used in a one-layer method (OLM) for long-term pancreas preservation before isolation of adult pig islets. METHODS: Resected pancreases were intraductally flushed with cold University of Wisconsin solution and immediately processed (n=6) or subjected to 7-hour storage by OLM (n=8) or TLM (n=10). Subsequently, pancreases were intraductally distended with collagenase NB-8 supplemented with neutral protease. Isolation and purification were performed as previously described. RESULTS: Compared with unstored pancreases (3,670+/-740 islet equivalents [IEQ]) purified islet yield in TLM-stored organs (2,080+/-290 IEQ, P<0.05) was significantly decreased in contrast with OLM-preserved pancreases (3,110+/-520 IEQ, NS). No differences were observed between groups regarding purity (>90%), trypan-blue exclusion (>95%), adenosine triphosphate content, and mitochondrial viability of islets. Stimulation index during static glucose incubation (20 vs. 2.8 mm) was decreased after storage by TLM (1.81+/-0.20, P<0.05) but not by OLM (2.27+/-0.57) if compared with unstored pancreases (2.47+/-0.36). However, transplantation into diabetic nude mice resulted in sustained normoglycemia of recipients of either group until nephrectomy of graft-bearing kidneys was performed. CONCLUSIONS: This study demonstrates that PFC alone can be used in a one-layer procedure for successful pig-pancreas preservation. This simplification can facilitate the broad application of PFC as pancreas preservation solution without reducing its benefits demonstrated by TLM.